2022
DOI: 10.1007/s00125-022-05765-8
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal lipid absorption and transport in type 2 diabetes

Abstract: Postprandial hyperlipidaemia is an important feature of diabetic dyslipidaemia and plays an important role in the development of cardiovascular disease in individuals with type 2 diabetes. Postprandial hyperlipidaemia in type 2 diabetes is secondary to increased chylomicron production by the enterocytes and delayed catabolism of chylomicrons and chylomicron remnants. Insulin and some intestinal hormones (e.g. glucagon-like peptide-1 [GLP-1]) influence intestinal lipid metabolism. In individuals with type 2 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 111 publications
1
25
0
1
Order By: Relevance
“…Similar findings were noted in previous studies from Turkey and India [19,22]. An increase in TC may be due to cholesterol absorption deficiency and higher cholesterol synthesis, especially among obese persons with diabetes, which suggests that diabetes modulates lipid metabolism [23,24].…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings were noted in previous studies from Turkey and India [19,22]. An increase in TC may be due to cholesterol absorption deficiency and higher cholesterol synthesis, especially among obese persons with diabetes, which suggests that diabetes modulates lipid metabolism [23,24].…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed that Apo-B levels are an independent risk factor for T2DM in the elderly Chinese population. Apo-B is a protein present on the surface of some lipoproteins, such as VLDL and LDL, which contain high levels of cholesterol ( Verges, 2022 ). The pancreas and other distal organs, such as the liver, receive lipids (cholesterol and triglycerides) via Apo-B ( Ying et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the metabolic demands of the sick subjects under experimentation; rats without metabolic alterations do not require nutrients available in the diet beyond those used for homeostatic balance. On the other hand, rats with DM require essential nutrients to compensate for the metabolic state of disease triggered by diabetes, using physiological digestive mechanisms and adaptations to absorb elements in the diet [93][94][95]. For example, studies suggest that in rats, diabetes induced by streptozotocin is connected to a rise in glucose absorption through the small intestinal mucosa [94,95] The observed out-of-range values in the Ctrl group in the serum biochemistry could be associated with a diet rich in fat, possibly produced by the oil used as the vehicle and the high protein in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, rats with DM require essential nutrients to compensate for the metabolic state of disease triggered by diabetes, using physiological digestive mechanisms and adaptations to absorb elements in the diet [93][94][95]. For example, studies suggest that in rats, diabetes induced by streptozotocin is connected to a rise in glucose absorption through the small intestinal mucosa [94,95] The observed out-of-range values in the Ctrl group in the serum biochemistry could be associated with a diet rich in fat, possibly produced by the oil used as the vehicle and the high protein in the diet. According to dietary recommendations for rodents, a diet with around 14% protein is considered ideal for their organic maintenance [96].…”
Section: Discussionmentioning
confidence: 99%